Bilateral uveal melanomas with different gene expression detected with 7 years interval. (24th October 2015) - Eide, Nils; Garred, Øystein; Beiske, Klaus; Fodstad, Øystein
Abstract: Purpose: To report a bilateral uveal melanoma detected in a micrometastasis study. Method: Case report. Results: At enucleation of a circumpapillary amelanotic mixed melanoma in a patient with ocular melanocytosis, a pigmented lesion in the other eye was detected, thought to be a naevus. BAP1 was positive showing nuclear staining of the tumour cells. Seven years later the naevus showed growth and development of a retinal detachment. FNAB disclosed monosomy 3 in the spindle tumour cells. Conclusion: A case of bilateral melanoma with long‐term survival without metastatic diseases is reported. Different gene expressions in the two eyes were revealed. The case is a reminder that follow‐up over years is essential in patients with a uveal melanoma, especially with ocular melanocytosis.